Neural correlates of altered sensorimotor gating in boys with Tourette Syndrome: A combined EMG/fMRI study. (2nd April 2016) - Buse, Judith; Beste, Christian; Herrmann, Elisabeth; Roessner, Veit
Abstract: Objectives : It has been hypothesised that altered sensorimotor gating might be a core problem in Tourette Syndrome (TS). However, the underlying neurophysiological mechanisms are elusive. Methods : We applied functional magnetic resonance imaging (fMRI) to investigate the neural correlates of altered sensorimotor gating by means of prepulse inhibition (PPI) in 22 boys with TS and 22 healthy boys using tactile PPI. The electromyography of the startle response was recorded simultaneously to the acquisition of the fMRI images. Results : As expected, PPI of the startle response was reduced in boys with TS compared to the healthy boys. We found decreased PPI-related blood oxygen level-dependent (BOLD) activity in boys with TS in the middle frontal gyrus, postcentral gyrus, superior parietal cortex, cingulate gyrus and caudate body. In boys with TS PPI of the startle response was positively correlated to PPI-related BOLD activity in the superior parietal cortex. Conclusions : Our findings indicate that deficient sensorimotor gating in boys with TS is associated with reduced recruitment of brain regions responsible for the higher-order integration of somatosensory stimuli. Due to our strict sample selection we were able to reduce confounding by neural adaptation processes, long-term medication, gender or comorbidities.